Uncover latent PPP by dynamic factor error correction model (DF-ECM) approach: Evidence from five OECD countries - Duo Qin (Queen Mary University of London, Department of Economics, 2006)
This study measures purchasing power parity (PPP) by means of the dynamic-factor errorcorrection model (DF-ECM) approach. Under this new approach, PPP is embedded in latent disequilibrium factors, which are extracted from a large variable set of bilateral price disparities; the factors are then used as error-correction leading indicators to explain exchange rate and inflation. Modelling experiments on five OECD countries using monthly data show promising results, which reverse the common belief that PPP is at best a very long-run relationship at the macro level.
Keywords: F31; C22; C33; 330; Purchasing power parity; Law of one price; Dynamic factor; Error correction; Kaufkraftparit\~AƒÂt; Fehlerkorrekturmodell; Dynamisches Modell; Sch\~AƒÂtzung; Kanada; Frankreich; Deutschland; Japan; Gro\~AƒÅbritannien